Wrong versus Right(eous): Online Reader Comments as Scientific Boundary‐Work. Issue 3 (6th April 2021) - Barker, Kristin Kay; Kenney, Alexis M.; Greene, R. Neil
Abstract : We bring a science‐as‐rhetoric framework, which has been used to study the claims of scientists, to examine lay claims about science. Using qualitative content analysis, we scrutinize the rhetoric of science in online reader comments sent in response to New York Times articles covering two recent measles outbreaks. Pro‐vaccine commenters use a variety of rhetorical tactics that simultaneously venerate science and denounce the antivaccination stance. These commenters, thus, participate in the ideological practices of boundary‐work to demarcate science from nonscience for the purposes of defeating their opponents and advancing their agenda. Our analysis foregrounds how and why this publics' demarcation of science is a type of moral crusade, that equates antiscientific beliefs with normative chaos. We situate our analysis in the larger cultural landscape wherein laypeople create "us" versus "them" using "science" as their wedge. The importance of developing sociological accounts of these dynamics has been made especially clear in the context of the COVID‐19 pandemic and its many science‐based controversies, including those related to vaccination.